Mediation of mammalian olfactory response by presence of odor-evoked potassium current - Hagerty, Samantha; Pustovyy, Oleg; Globa, Ludmila; Vodyanoy, Vitaly; Singletary, Melissa (Frontiers in Allergy, 2024)
It is well understood that odorants interact with specialized G-protein coupled receptors embedded in the ciliary membrane of olfactory sensory neurons (OSN) which initiates a voltage-generating intracellular cascade of signal transduction events that can be recorded at the epithelial level as an electroolfactogram (EOG). While the depolarizing excitatory pathway in vertebrates involving cyclic adenosine monophosphate (cAMP)-induced Na+/Ca2+ influx and calcium-induced Cl− efflux is well established, there is evidence of potassium-associated inhibitory currents that correspond with cellular activation. While several Ca2+-dependent feedback mechanisms contribute to cellular deactivation which have been commonly attributed to these inhibitory currents, the frequently observed positive ionic conductance prior to excitatory depolarization have led many to suggest an additional earlier inhibitory mechanism at the receptor level that may be independent of downstream calcium influx. Due to conflicting conclusions, the role and mechanism behind Ca2+-independent inhibitory currents in olfactory cells is not fully understood. We investigated the functional and temporal involvement of potassium channels in odor transduction by comparing electroolfactogram (EOG) recordings in rat olfactory epithelia following ion channel inhibition and targeted activation of downstream components with or without potassium-blocking. Several K+-channel blocking agents (4-Aminopyridine, charybdotoxin, & iberiotoxin) demonstrated a diminished pre-action potential positive current that corresponded with reduced excitatory response to odor stimulation that was recovered when blockers were removed. We further assessed EOG responses in the absence of odor or with odor response enhancing zinc nanoparticles. Chemically eliciting membrane excitation in the absence of odor stimulation with a phosphodiesterase inhibitor, 3-isobutyl-1-methylxanthine (IBMX), in combination with K+-channel inhibition, further indicated potassium channel activation precedes excitatory events and is independent of cAMP-induced calcium influx. These results support previous findings of odor-activated inhibitory potassium currents that may play a functional role in subsequent G-protein activity.